Preliminary Investigation of Risk Factors for Food Allergies in the Pediatric Population: Observations from a Survey Utilizing a Simplified Questionnaire in Gresik, East Java, Indonesia - Jahja, Natalia Erica; Hikmah, Zahrah; Putera, Azwin Mengindra; Endaryanto, Anang (Folia Medica Indonesiana, 2024)
Highlights: 1. A questionnaire, comprising various risk factors associated with food allergies, is anticipated to provide reliable indications for determining the necessity of restrictive diets for patients within primary healthcare settings. 2. Over time, the findings of this study can facilitate the development of a streamlined and cost-effective diagnostic tool, which will be particularly beneficial in remote regions due to its practical and efficient means of identifying food allergies. Abstract In Gresik, Indonesia, limited resources have led to challenges in accurately diagnosing food allergies. This study aimed to identify risk factors for food allergies among children in Gresik using a questionnaire-based approach. The study's ultimate goal was to develop a simple diagnostic tool in primary healthcare settings. Conducted at Petrokimia Gresik Hospital, this cross-sectional study enrolled children aged â‰¥6 months experiencing respiratory symptoms or atopic dermatitis for â‰¥1 week. The subjects (n = 247) underwent a two- to four-week restrictive diet for diagnostic purposes. The questionnaire demonstrated validity and reliability. Bivariate statistical analyses were performed to examine the correlations between risk factors and the incidence of food allergies (p < 0.05). A receiver operating characteristic (ROC) curve analysis was used to establish the cut-off values for the number of food allergies and atopic family members. The majority of the 247 children enrolled in this study were 6 to 12 years old. Respiratory symptoms (56.3%) were more common than atopic dermatitis (38.1%). The significant risk factors for food allergies included atopic dermatitis (p = 0.001; R = 0.203), previous history of suspected food allergies (p < 0.001; R = 0.747), and atopy in the family (p = 0.013; R = 0.157). The ROC curve analysis established the cut-off values for the number of atopic family members at 1.5 (p = 0.005; 95% CI 0.53-0.67) and the number of food allergies at 0.5 (p = 0.000; 95% CI 0.85-0.94). In conclusion, children are considered at risk of food allergies if they display persistent respiratory symptoms or atopic dermatitis, considering the history of suspected food allergies even to only one specific type of food.